Analysis on profit model of multi‐information products logistics using evolutionary game algorithm. (18th October 2018) - Yang, Bo
Summary: Agricultural products logistics finance warehouse business mainly includes three parties: agricultural production and processing enterprises and the third‐party logistics enterprises and financial institutions, to allow three parties to achieve a win‐win situation; in this paper, the evolutionary game theory is used to construct the evolutionary game model of three‐party selection different strategies and, through the construction of replicated dynamic equation, solving the evolution stable strategy. At last, based on the evolutionary stable point, the paper analyzes the strategies of agricultural production and processing enterprises, the third‐party logistics enterprises and financial institutions, and gives the feasible suggestions to the three‐party strategy. Realization of agricultural products logistics finance warehouse profit model three‐party mutual benefit and win‐win, so as to promote the smooth development of agricultural products logistics financial business, ensure the cooperation and common development of agricultural production and processing enterprises and the third‐party logistics enterprises.